A study to assess the knowledge of medical students regarding organ donation in a selected college of Western Maharashtra - Apoorva Sindhu; T S Ramakrishnan; Anurag Khera; Gurpreet Singh (Medical Journal of Dr. D.Y. Patil University, 2017)
Context: As per United Network for Organ Sharing, there are over 71,000 people on organ transplant waiting list in the United States. The only way to increase organ donations is to educate the health-care professionals and public about the importance of becoming an organ donor. One of the ways to start this is to promote the awareness of the college students, especially those in the medical field, toward organ donation as they are the most suitable persons to carry the message to the community. Aims: This study aims to determine the knowledge of medical students regarding organ donation. Settings and Design: Cross-sectional study conducted in a medical college of Western Maharashtra. Subjects and Methods: A questionnaire adapted to the study requirements from the published research was designed to capture the knowledge toward organ donation. Final year MBBS students who gave verbal consent to the study were included. Statistical Analysis Used: Microsoft Excel and SPSS version 20. Results: 87% of the students had correct knowledge regarding brain death occurring after road traffic accident. Fifty-four percent (54.45%) of students were not aware that an individual suffering from infectious disease cannot donate organs. 61% of the students were not aware that a National network for organ donation exists in their city. 48.5% of students did not know how to register oneself as an organ donor. Conclusions: The results of the study revealed that there exists a knowledge gap among the medical students regarding organ donation and there is an urgent need for addressing this knowledge gap which will help in improving the organ donation rate in our country.